Experimental study on mechanical properties of the steel friction pads used in a rotational friction damper. (February 2021) - Sui, Weining; Wang, Xueli; Wang, Zhanfei
Abstract: The optimal friction interface offered by friction pads should have stable frictional energy consumption performance, be easily fabricated, and satisfy the structure durability requirements imposed by use in civil engineering operations. In this paper, firstly, to assess the friction performance of the friction pads, a new clamping set-up equipped with a high-strength bolt was proposed for use as a friction-damping device. Then an experimental study was conducted with the clamping set-up on six different types of friction pad specimens. The main parameters are the mechanical properties, the friction interface area, the superficial treatment method applied to the steel friction pads, and the loading protocol. The experimental results indicate that: the load–displacement hysteresis curves are stable and exhibit no degradation in behaviour throughout the test, suggesting that the energy absorption performance of the friction damper is significant; the friction damper exhibit significant initial stiffness, showing that the rotational friction damper can provide stiffness for frame structures before rotation; the coefficient of friction of the friction pads is found to be influenced by the mechanical properties; in addition, the load–displacement hysteresis curve in the second loading stage is more stable than that in the first loading stage.